NK Cells Negatively Regulate CD8 T Cells to Promote Immune Exhaustion and Chronic Toxoplasma gondii Infection - Ivanova, Daria L.; Krempels, Ryan; Denton, Stephen L.; Fettel, Kevin D.; Saltz, Giandor M.; Rach, David; Fatima, Rida; Mundhenke, Tiffany; Materi, Joshua; Dunay, Ildiko R.; Gigley, Jason P. (Frontiers in Cellular and Infection Microbiology, 2020)
NK cells regulate CD4+ and CD8+ T cells in acute viral infection, vaccination, and the tumor microenvironment. NK cells also become exhausted in chronic activation settings. The mechanisms causing these ILC responses and their impact on adaptive immunity are unclear. CD8+ T cell exhaustion develops during chronic Toxoplasma gondii (T. gondii) infection resulting in parasite reactivation and death. How chronic T. gondii infection impacts the NK cell compartment is not known. We demonstrate that NK cells do not exhibit hallmarks of exhaustion. Their numbers are stable and they do not express high PD1 or LAG3. NK cell depletion with anti-NK1.1 is therapeutic and rescues chronic T. gondii infected mice from CD8+ T cell exhaustion dependent death, increases survival after lethal secondary challenge and alters cyst burdens in brain. Anti-NK1.1 treatment increased polyfunctional CD8+ T cell responses in spleen and brain and reduced CD8+ T cell apoptosis in spleen. Chronic T. gondii infection promotes the development of a modified NK cell compartment, which does not exhibit normal NK cell characteristics. NK cells are Ly49 and TRAIL negative and are enriched for expression of CD94/NKG2A and KLRG1. These NK cells are found in both spleen and brain. They do not produce IFNγ, are IL-10 negative, do not increase PDL1 expression, but do increase CD107a on their surface. Based on the NK cell receptor phenotype we observed NKp46 and CD94-NKG2A cognate ligands were measured. Activating NKp46 (NCR1-ligand) ligand increased and NKG2A ligand Qa-1b expression was reduced on CD8+ T cells. Blockade of NKp46 rescued the chronically infected mice from death and reduced the number of NKG2A+ cells. Immunization with a single dose non-persistent 100% protective T. gondii vaccination did not induce this cell population in the spleen, suggesting persistent infection is essential for their development. We hypothesize chronic T. gondii infection induces an NKp46 dependent modified NK cell population that reduces functional CD8+ T cells to promote persistent parasite infection in the brain. NK cell targeted therapies could enhance immunity in people with chronic infections, chronic inflammation and cancer.